Modified and Improved TID Controller for Automatic Voltage Regulator Systems - Abdulsamed Tabak (Fractal and Fractional)
This paper proposes a fractional order integral-derivative plus second-order derivative with low-pass filters and a tilt controller called IλDND2N2-T to improve the control performance of an automatic voltage regulator (AVR). In this study, equilibrium optimisation (EO), multiverse optimisation (MVO), and particle swarm optimisation (PSO) algorithms are used to optimise the parameters of the proposed controller and statistical tests are performed with the data obtained from the application of these three algorithms to the AVR problem. Afterwards, the performance of the IλDND2N2-T controller is demonstrated by comparing the transient responses with the results obtained in recently published papers. In addition, extra disturbances such as frequency deviation, load variation, and short circuit faults in the generator are applied to the AVR system. The proposed controller has outperformed the compared controller against these disturbances. Finally, a robustness test is performed in terms of deterioration in the system parameters. The results show that the IλDND2N2-T controller outperforms the compared controllers under all conditions and exhibits a robust effect on the perturbed system parameters.